INDEX OF THE CYCLE OF MONEY - THE CASE OF HUNGARY - Challoumis, Constantinos (Economica, 2024)
This paper has mounted the index of the cycle of money. According to the idea of the cycle of money, it is tested if an amount of cash is recycled inside the financial system in a variety of instances or if this amount of cash is misplaced from a financial system to different economies or banks abroad, due to the now no longer good enough structure of the financial system of the country. The reason for the paper is to expose the utility of the case cycle of money, right here for the case of Hungary. Therefore, this work goal is to make clear how the concept of the cycle of money, works in an actual case scenario and is well known how the cycle of money applies to an economic system. Moreover, the index of the cycle of money suggests how an economic system ought to counteract a monetary crisis and how well-structured it is. The estimations of the index of the cycle of money in the case of Hungary are compared with the global average index of the cycle of money. The estimations indicate as expected that Hungary is above the average global value. Hungary's findings reveal that it is a well-structured economy and can face an economic crisis. Prior papers are from the case of Latvia, Serbia, Greece, Bulgaria, Ukraine, Thailand, and Poland. This work is part of a project for multiple countries. The results are the first in the bibliography about the cycle of money of Hungry through the application of this theory.